2019
DOI: 10.3892/ijmm.2019.4184
|View full text |Cite
|
Sign up to set email alerts
|

Nur77 promotes cigarette smoke‑induced autophagic cell death by increasing the dissociation of Bcl2 from Beclin-1

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by partially reversible airflow limitation and persistent alveolar destruction, and autophagy is involved in the pathogenesis of cigarette smoke (CS)-induced COPD. Nuclear receptor 77 (Nur77) participates in a number of biological processes, including apoptosis, autophagy and in disease pathogenesis; however, the role of Nur77 in COPD remains unknown. Thus, in this study, we aimed to elucidate the role of Nur77 in COPD. We report that CS promotes Nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
0
11
1
Order By: Relevance
“…Contrasting with our findings, Qin et al reported that CS and CSE increased, rather than suppressed, Nur77 in lungs of mice or HBE cells and enhanced Nur77 nuclear export with a concurrent increase in autophagy of the cells [37]. Resolving this discrepancy will require further study, but we speculate that it is attributable to time-dependent differences in CS-induced alteration of Nur77 expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrasting with our findings, Qin et al reported that CS and CSE increased, rather than suppressed, Nur77 in lungs of mice or HBE cells and enhanced Nur77 nuclear export with a concurrent increase in autophagy of the cells [37]. Resolving this discrepancy will require further study, but we speculate that it is attributable to time-dependent differences in CS-induced alteration of Nur77 expression.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, Dendrogenin A, a mammalian cholesterol metabolite ligand of liver-X-receptors (LCRs) induces Nr4a1 expression in association with excessive autophagic cell death both in vitro and in vivo [15,16], displaying anticancer and chemopreventive properties in mice [17]. Interestingly, NR4A1 interaction with anti-apoptotic BCL2 family members outside the BH3 domain induces autophagic cell death [18], which seems to be mediated by releasing BECN1 in a model of cigarette smokeinduced autophagic cell death [19]. Taken together, these findings indicate that NR4A1 could function as a broad inducer of autophagic cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Dendrogenin A, a mammalian cholesterol metabolite ligand of liver-X-receptors (LCRs) induces Nr4a1 expression in association with excessive autophagic cell death both in vitro and in vivo (15, 16), displaying anticancer and chemopreventive properties in mice(17). Interestingly, NR4A1 interaction with anti-apoptotic BCL2 family members outside the BH3 domain induces autophagic cell death (18), which seems to be mediated by releasing BECN1 in a model of cigarette smoke-induced autophagic cell death(19). Taken together, these findings indicate that NR4A1 could function as a broad inducer of autophagic cell death.…”
Section: Introductionmentioning
confidence: 99%